1977
DOI: 10.1172/jci108759
|View full text |Cite|
|
Sign up to set email alerts
|

Glucagon and Insulin Binding to Liver Membranes in a Partially Nephrectomized Uremic Rat Model

Abstract: A B S T R A C T To investigate the role of glucagon and insulin receptor binding in the glucagon hypersensitivity and insulin resistance which characterize the glucose intolerance of uremia, liver plasma membranes were prepared from control rats (blood urea nitrogen [BUN] 15±1 mg/100 ml, creatinine 0.7±0.2 mg/100 ml), and from 70% nephrectomized rats (BUN 30±2 mg/100 ml, creatinine 2.2±0.2 mg/100 ml), and from 90% nephrectomized rats (BUN 46±3 mg/100 ml, creatinine 4.20+0.7 mg/100 ml), 4 wk after surgery. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

1978
1978
1985
1985

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 36 publications
(37 reference statements)
2
19
2
Order By: Relevance
“…Studies by Sherwin et al (23) have shown that the liver ofchronically uremic subjects displays enhanced sensitivity to the stimulatory effect of glucagon on hepatic glucose production. In subsequent studies Soman and Felig (24) suggested that this higher sensitivity was due to increased glucagon binding to hepatic membranes with a resultant increase in cyclic AMP generation. Thus, it is possible that during conditions in which glucagon is increased, i.e., pure protein feeding or a mixed protein-carbohydrate meal, the suppression of hepatic glucose production by insulin may be incomplete.…”
Section: Discussionmentioning
confidence: 98%
“…Studies by Sherwin et al (23) have shown that the liver ofchronically uremic subjects displays enhanced sensitivity to the stimulatory effect of glucagon on hepatic glucose production. In subsequent studies Soman and Felig (24) suggested that this higher sensitivity was due to increased glucagon binding to hepatic membranes with a resultant increase in cyclic AMP generation. Thus, it is possible that during conditions in which glucagon is increased, i.e., pure protein feeding or a mixed protein-carbohydrate meal, the suppression of hepatic glucose production by insulin may be incomplete.…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that as a result of increased absorption greater amounts of glucose would be taken up by the liver. The liver is in turn subject to the increased sensitivity of the glucose-elevating effect of glucagon present in uremia (4,28,30). The increase in glucose absorption was proportionate to the concentration of glucose in the solutions perfused, with comparable differences at 4 and 40 mM between uremic and control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Liver membranes (8)(9)(10)(11)(12) Mg protein) were incubated for 10 min at 30°C in a final volume of 50 Ml containing 0.1 mM [a-32P]ATP (1,000-1,500 cpm/pmol), 5 mM MgCI2, 1 mM EDTA, 1 mM[3H]cAMP (-10,000 cpm), 25 mM Tris-HCI, the indicated additives, and an ATP-regenerating system consisting of 0.02 mg/ml myokinase, 0.2 mg/ml creatine phosphokinase, and 20 mM creatine phosphate. The incubations were terminated by the addition of 100 Ml of a stop solution consisting of 40 mM ATP, 10 mM ofcAMP, and 1% sodium dodecyl sulfate.…”
Section: Adenylyl Cyclase Assaysmentioning
confidence: 99%
“…These increased immunoreactive glucagon levels result from increases in a number of molecular weight species, each of which may have glucagon-like immunoreactivity if not biological activity (6)(7)(8). Glucagon-stimulable adenylyl cyclase activity in liver of uremic rats has been found to be increased (9,10). Other more indirect assessments have inferred a decreased activity of this enzyme in chronic uremia (1 1).…”
Section: Introductionmentioning
confidence: 99%